Optimization of automated external defibrillator deployment outdoors: An evidence-based approach. (November 2016) - Dahan, Benjamin; Jabre, Patricia; Karam, Nicole; Misslin, Renaud; Bories, Marie-Cécile; Tafflet, Muriel; Bougouin, Wulfran; Jost, Daniel; Beganton, Frankie; Beal, Guillaume; Pelloux, Patricia; Marijon, Eloi; et al.
Abstract: Background: The benefits of available automatic external defibrillators (AEDs) for out-of-hospital cardiac arrests (OHCAs) are well known, but strategies for their deployment outdoors remain somewhat arbitrary. Our study sought to assess different strategies for AED deployment. Methods: All OHCAs in Paris between 2000 and 2010 were prospectively recorded and geocoded. A guidelines-based strategy of placing an AED in locations where more than one OHCA had occurred within the past five years was compared to two novel strategies: a grid-based strategy with a regular distance between AEDs and a landmark-based strategy. The expected number of AEDs necessary and their median (IQR) distance to the nearest OHCA were assessed for each strategy. Results: Of 4176 OHCAs, 1372 (33%) occurred in public settings. The first strategy would result in the placement of 170 AEDs, with a distance to OHCA of 416 (180–614) m and a continuous increase in the number of AEDS. In the second strategy, the number of AEDs and their distance to the closest OHCA would change with the grid size, with a number of AEDs between 200 and 400 seeming optimal. In the third strategy, median distances between OHCAs and AEDs would be 324 m if placed at post offices (n = 195), 239 at subway stations (n = 302), 137 at bike-sharing stations (n = 957), and 142 at pharmacies (n = 1466). Conclusion: This study presents an original evidence-based approach to strategies of AED deployment to optimize their number and location. This rational approach can estimate the optimal number of AEDs for any city.